Physical exercise alone or combined with omega-3 modulates apical periodontitis induced in rats - Ribeiro, Ana Paula Fernandes [UNESP]; de Lima Rodrigues, Michely [UNESP]; Loureiro, Caroline [UNESP]; Machado, Nathalia Evelyn da Silva [UNESP]; Cantiga-Silva, Cristiane [UNESP]; de Oliveira, Pedro Henrique Chaves [UNESP]; Cintra, Lucino Tavares Angelo [UNESP]; Jacinto, Rogério de Castilho [UNESP] (Springer Nature, 2025)
Apical periodontitis (AP) results from bacterial contamination of the pulp tissue, with its progression highly influenced by the host’s immune response. This study aimed to evaluate the impact of moderate physical exercise, alone or combined with omega-3 supplementation, on AP induced in rats. The analysis focused on the immuno-inflammatory profile, bacterial presence in the root canal and apical region, bone loss, and collagen fiber production. Thirty Wistar rats were divided into three groups: Control, Physical Exercise (PE), and Physical Exercise + Omega-3 (PEO). Omega-3 supplementation was administered by gavage for 60 days. The swimming protocol included two stages: acclimatization to the aquatic environment and swimming training. AP was induced on the 30th day, and the rats were euthanized on the 60th day. Upper molars were processed and stained using Hematoxylin and Eosin (H&E), Brown and Brenn (BB), Picrosirius Red (PSR), and immunohistochemistry for IL-17, TNF-α, and tartrate-resistant acid phosphatase (TRAP). Microtomographic analysis was also performed. Scores from the analyses were evaluated using Kruskal-Wallis, Tukey, Shapiro-Wilk, Mann-Whitney, and One-Way ANOVA tests, with a significance level of 5% (p < 0.05). The control group exhibited the highest intensity of inflammatory infiltrate (p < 0.05). PE alone reduced TNF-α immunostaining and limited bacterial spread (p < 0.05). Combined with omega-3 supplementation, PE further reduced IL-17 immunostaining and increased the percentage of birefringent immature collagen fibers (p < 0.05). Microtomographic analysis revealed smaller areas of alveolar bone loss in animals subjected to PE (p < 0.05). The control group showed a significantly higher number of TRAP-positive cells (p < 0.05). In conclusion, PE alone enhanced defense mechanisms by reducing inflammation through TNF-α modulation and controlling bacterial contamination. Combined with omega-3 supplementation, PE further improved inflammatory regulation by modulating IL-17 levels, reducing bone loss, and stimulating collagen production, thereby limiting inflammation and decreasing osteoclastic activity.
Keywords: Apical periodontitis; Endodontics; Exercise; Omega 3 fatty acid; Swimming